Effectiveness of Autologous Platelet Concentrates in the Sinus Lift Surgery: Findings from Systematic Reviews and Meta-Analyses - Roberta Gasparro; Alessandro Espedito Di Lauro; Maria Domenica Campana; Nicola Rosiello; Mauro Mariniello; Gilberto Sammartino; Gaetano Marenzi (MDPI AG, 2024)
Maxillary sinus augmentation is one of the most predictable procedures for the rehabilitation of the posterior maxilla. The current overview aimed to summarize the findings provided by systematic reviews (SRs) and meta-analyses on the effectiveness of autologous platelet concentrates (APCs) in sinus lift and to assess the methodological quality of the included SRs. Three electronic databases have been explored. SRs and meta-analyses addressing the effectiveness of APCs in sinus lift technique were included. Clinical, radiographic and histomorphometric findings were considered for APCs as solely grafting materials and APCs in combination with biomaterials. Outcomes were implant survival rate (ISR), implant stability (IS), implant failure (IF), postoperative complications, histomorphometric findings, radiographic bone gain, bone volume and bone density. The methodological quality of the included SRs was assessed using the updated version of "A Measurement Tool to Assess Systematic Review" (AMSTAR-2). Thirty SRs were included. The methodological quality of the included reviews ranged from critically low (3 studies) to high (9 studies). The included SRs showed favorable clinical outcomes, short-term new bone formation and no biological complications when APCs were used both as solely graft material or in combination with other biomaterials. However, no significant additional effects in the long-term period were observed. APCs did not add any further positive effects compared to the physiological healing derived by the natural blood clot. The current overview of SRs highlighted the need for high-quality SRs evaluating the role of APCs in sinus lift though network meta-analyses, in order to identify the most powerful material for sinus lift augmentation. The use of APCs improves the healing of soft tissues and the postoperative quality of life in the short-term period. Thus, its application can be recommended.